The Emergence of Multi-Messenger Astronomy, Part I: Supernovae as Epistemic Laboratories. - LA RANA, ADELE; BONOLIS, LUISA; LALLI, ROBERTO (Centaurus: Journal of the European Society for the History of Science, 2025)
The paper explores the historical development of supernova research in the 20th century and examines its role in the emergence of multi-messenger astronomy. Through an analysis of primary scientific literature and review sources, we show that theoretical and experimental investigations of supernovae, from the 1930s to the supernova 1987A and beyond, have fostered a crucial shift in astronomical research. Building on conceptual tools from history of science and social studies--such as Galison's "trading zones," Star and Griesemer's "boundary objects," and Renn's notions of "challenging objects" and "borderline problems"--this analysis shows how supernovae served as both enablers and drivers of productive confrontation and exchanges across disciplinary boundaries. Through key episodes we discuss how they bridged different research domains, shaping hybridized practices and expertise, in order to address complex questions that no single field could resolve. Particular attention is given to the detection of SN1987A. Though not yet embedded in a mature multi-messenger framework, it revealed the latent infrastructure, interpretive gaps, and epistemic promise of a globally coordinated, real-time, multi-signal astronomy, anticipating more integrated approaches. Following this turning point, the article traces how collaborative practices gradually solidified into enduring forms of interdisciplinary work, laying the epistemic groundwork for multi-messenger science long before the term gained currency. We argue that supernova research functioned as a long-term trading zone, where experimental practices, theoretical models, and instrumentation co-evolved across disciplinary boundaries. By reconstructing this process, the paper contributes to a historical understanding of how new scientific fields emerge through the reconfiguration of existing ones. This paper forms the first part of a twofold study on the emergence of multi-messenger astronomy as a new field of scientific inquiry. The companion study will integrate this contribution, by tracing the rise and consolidation of multi-messenger research networks through co-authorship and co-citation analysis in the 21st century.